Informed Consent sebagai Upaya Perlindungan Hukum Bagi Tenaga Kesehatan dalam Kasus Medis Darurat (Studi Kasus di Rumah Sakit Umum Daerah Provinsi Papua Barat) - Winarti, Winarti; Rizka, Rizka (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
This study aims to analyse the role of informed consent, legal protection and health workers in the Regional General Hospital of West Papua Province. The research method used is a quantitative approach. The data analysis used was verification analysis using linear regression analysis. The verification method is used to test the relationship between variables. The sample consisted of 35 respondents who were taken using saturated sampling technique. The results of this study indicate that there is a significant influence between the variables of informed consent and legal protection of health workers in medical practice, especially in the context of health services in emergency situations. The results of hypothesis testing show that the application of informed consent serves as a guarantee for patients to understand the medical procedures to be carried out, while protecting health workers from potential lawsuits. Law No. 17 of 2023 provides a clear legal framework regarding the obligation of health workers to obtain consent for medical actions, with the exception of emergencies. This study confirms the importance of effective communication between health workers and patients. Although health workers do not fully understand the principles of informed consent.